(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
A field experiment was conducted in the Ministry ofAgriculture and Animal Resources Farm in the Red Sea coast at Arim, fortwo seasons (2011/2012 and 2013/2014) to investigate the effect ofdiluted Red Sea waters on the growth and productivity of sorghum(Sorghum bicolor) in a Typic Torrifluvent soil. The treatments consistedof three varieties: forage sorghum (Abusabien), Aklomoy and White milo,three dilutions of Red Sea water with three electrical conductivities(ECiw): 0.48, 5.4, and 9.4 dS/m, and three replicates. The treatments werearranged in a split-plot design, where ECiw treatments designated themain plots and sorghum varieties the subplots. Soil samples werecollected before planting and at harvest by an auger from the followingfive successive depths: 0-10, 10-20, 20-40, 40-60, and 60-100 cm. In bothseasons, the overall mean height (H) for the three varieties showedsignificant (P < 0.05) linear decrease with increase of ECiw. At harvest,Abusabien gave highly significant (P < 0.01) tallest plants while whitemilo gave the shortest plants. The mean plant heights of Abusabien,Aklamoy and White milo in the first season were 156, 121 and 116 cm,respectively. In the second season the mean heights for the same varietiesin sequence were 173, 147 and 125 cm. The main effects of ECiw, varietyand their interaction on leaf area index (LAI) were not significant in thefirst season and the overall mean LAI was 3.8. In the second season, the